Career development across the lifespan : counseling for community, schools, higher education, and beyond - Eliason, Grafton; Lepore, Mark; Samide, Jeff L.; Patrick, John, 1955- (Emerald Publishing Limited : Information Age Publishing Inc., 2019)
This second edition of Career Counseling Across the Lifespan: Community, School, Higher Education, and Beyond is the latest volume in the Issues in Career Development Series, edited by Drs. Grafton Eliason, Mark Lepore, Jeff Samide, and John Patrick, from California University of Pennsylvania and Clarion University of Pennsylvania. The purpose of Career Development Across the Lifespan is to provide a broad and in-depth look at the field of career development as it applies to individuals involved in all areas of community counseling, school counseling, and higher education. The book will examine some of the field's major theories, themes, approaches, and newest models incorporating chapters from national and international career counseling experts. Specific emphasis is spent examining issues reflective of today's challenges in developing and maintaining a workforce that is diverse, flexible, and efficient. Readers will be provided with an action-based framework built on the best available research.This text book is truly the culmination of a decade's work, compiling comprehensive studies from four previous volumes and updating key concepts in career counseling with the most contemporary theories and innovations. We examine three primary domains of career counseling throughout all of the developmental stages of the lifespan: community, schools K-12, and higher education. We include a specific focus on career history and theories, to prepare students for both the counseling environment and for national exams leading to certification and licensure, such as the (NCE) National Counseling Exam. We also include cutting edge research on contemporary topics, including such areas as: military careers, life after the military, individuals with disabilities or special needs, career counseling in our current socio-economic environment, and current technologies such as virtual counseling. In addition, we have added case studies and key terms as study guides at the end of each chapter. We are fortunate to include many recognized experts in the field of career counseling. Career Counseling Across the Lifespan: Community, School, Higher Education, and Beyond is a comprehensive text, written to address the broad needs of career counselors, educators, and students today.
Keywords: Career development.; Vocational guidance.; Education -- Counseling -- Career Development.; Educational strategies and policy.; Careers guidance.; elektronické knihy; electronic books